People's Understanding of the Off-Court Talak (Case Study in Nagari Koto Tuo, IV Nagari District, the Sijunjung Regency) - Merlin Putri; Shafra Shafra (IAIN Padangsidimpuan, 2021)
This study describes the understanding of the people of Nagari Koto Tuo, IV Nagari District, The Sijunjung Regency about divorce (talak) outside the Religious Court. Ideally, with the enactment of Law No. I of 1974 on marriage, talak should be decided in the Religious Court. However, this ideal procedure does not apply effectively in Nagari Kuto Tuo. Although the local settlement is not distant to the local Religious Court and the access for transportation is easy, many husbands recklessly decide to divorce their wives at home during the dispute between them without registering their lawsuits to the court. The purpose of this study is to lower the off-court divorce rate and raise legal awareness of the public about the importance of following the prevailing regulation regarding divorce in Indonesia. This is important because divorces decided without statutory procedures have adverse impacts, especially for women and children. This study uses a qualitative approach, with the divorced wives being the subject of the study. The data collection techniques include observation, interviews and documentation. Data validity techniques follow the triangulation method, whereas data analysis is performed through the following steps: data collection, data reduction, data presentation and conclusion drawing. This study found that the understanding of the people in Nagari Koto Tou about divorce is shaped by classical Islamic jurisprudence (fiqh) that posits husband to have the absolute right to divorce. With this absolute right, husbands can decide to divorce their wives whenever and wherever they want without being bothered to consider registering it formally to the local Religious Court. The divorced wives are left in despair without any power to defend her right. This provision on divorce is considered indisputable let alone contested. As a consequence, this off-court divorce generally leaves women traumatized, making many of them unwilling to get another marriage. This trauma partly contributes to the number of off-court marriages, for they do not see its importance. Legal certainty obtained from the court's verdict of divorce as recorded by the divorce certificate is deemed unnecessary, for they would not remarry in the future